Dampak Psikologis Anak Yang Diterlantarkan Dikota Kupang Nusa Tenggara Timur - Tsiompah, Eduarda D.; Wijaya, RPC; Manafe , Rizky (Ridwan Institute, 2025)
This study examines the psychological impacts experienced by children who are left behind due to parental migration in Kupang City, East Nusa Tenggara. Using a qualitative approach with a phenomenological method, data were collected through photovoice techniques and semi-structured interviews. Five children aged 10 to 19 participated in this study. The analysis revealed three main themes: (1) the resilience of children in coping with parental separation, (2) deep longing for the presence of parents, and (3) discomfort in household life during the absence of parents. Social support from the surrounding environment and the role of surrogate caregivers, such as grandparents, proved to be significant factors in the emotional well-being of the children. However, the psychological needs of these children are often neglected. This study recommends the necessity of more humane interventions and policies that are responsive to the conditions of children affected by parental migration to ensure their optimal growth and development amid family separation. situations.